Chitosan/Cellulose Nanofibril Nanocomposite and Its Effect on Quality of Coated Strawberries - N. S. Resende; G. A. S. Gonçalves; K. C. Reis; G. H. D. Tonoli; E. V. B. V. Boas (Journal of Food Quality)
The aim of this study was to develop a chitosan/cellulose nanofibril (CNF) nanocomposite and evaluate its effect on strawberry’s postharvest quality after coating. From the results of color, thickness, and scanning electron microscopy (SEM) and permeability to water vapor analyses, the best film formulation for coating strawberries was determined. Three coating formulations were prepared: 1% chitosan, 1% chitosan + 3% CNF, and 1% chitosan + 5% CNF. The strawberries were immersed in the filmogenic solutions and kept under cold storage (1 ± 1°C). The color of the film was not affected by increased concentration of cellulose nanofibrils; however, the thickness and water vapor permeability were affected by the CNF addition. The coating with the highest CNF concentration performed better in reducing fruit mass and firmness loss. The color was positively influenced by the addition of the coating, regardless of formulation, as well as soluble solid content, PG enzymatic activity, and the fruit appearance. The pH and titratable acidity showed no significant difference among treatments. It was observed that the vitamin C, phenolic compounds, and anthocyanin content, as well as the PAL activity and the antioxidant activity (except for % protection), were affected by chitosan coating, however not by the addition of CNFs.